2014
DOI: 10.1075/ni.24.2.01lin
|View full text |Cite
|
Sign up to set email alerts
|

“What happened when you came to Sweden?”

Abstract: Depicted as someone without agency, with no free will and completely in the hands of the trafficker, the ideal trafficking victim can be seen as diametrically different from the guilty prostitute. By analysing how responsibility and victimhood are negotiated in forensic interviews with alleged adolescent trafficking victims, this article scrutinises this image by asking how victim-status is handled when questions turn to sex and prostitution and which interactive and narrative conditions, related to agency, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This victim-blaming has been found to be part of many institutional encounters (Drew 1992;Jokila 2010;Keskinen 2005;Lindholm, Börjesson, and Cederborg 2014;Matoesian 2000). This study found that it was especially a discourse used by child protection, and that it was used to blame mothers for their children's -and their ownvictimization by fathers.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…This victim-blaming has been found to be part of many institutional encounters (Drew 1992;Jokila 2010;Keskinen 2005;Lindholm, Börjesson, and Cederborg 2014;Matoesian 2000). This study found that it was especially a discourse used by child protection, and that it was used to blame mothers for their children's -and their ownvictimization by fathers.…”
Section: Discussionmentioning
confidence: 72%
“…This victim-blaming is very common in many different sites, where responsibility for violence is defined (Drew 1992;Hart and Bagshaw 2008;Jokila 2010;Keskinen 2005;Lindholm, Börjesson, and Cederborg 2014;Matoesian 2000). The conflict discourse was gendered in the ways in which it disregarded gender in cases of fathers perpetrating violence towards mothers and children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, women reporting rape to police orient to 'rape myths' as common-sense ways to make sense of their experiences and accounted for their behaviour to pre-empt blame (MacLeod, 2016). The common-sense association between victims and passivity means attributions of responsibility in police interviews invalidate women's victim membership and officers' accompanying obligation to help them (Lindholm, Börjesson, and Cederborg, 2014). Thus, categorising victims and crimes is part of the "micro-politics of everyday and institutional life" (Baker, 2000, p. 99).…”
Section: Introductionmentioning
confidence: 99%
“…Analysing disclosures as they occur can demonstrate how cultural understandings of gender and violence occur in practice. For example, Lindholm, Börjesson Cederborg (2014) examined police interviews where officers attempted to determine if women were victims of trafficking, or sex workers of their own volition. Through narrative analysis, the authors documented how discourses and moral hierarchies of victimhood were invoked by emphasising either responsibility or passivity.…”
Section: Introductionmentioning
confidence: 99%